Living beings as autopoietic bodies. (February 2020) - Villalobos, Mario
In the target article, it was claimed that the enactive extended interpretation of the autopoietic theory (AT) of living beings is incorrect, and an embodied reformulation of AT (EAT) was put forward to remedy and prevent such an interpretation. In this general reply, I want to clarify the motivation, reach, philosophical commitments, and theoretical status of EAT. I do this, mainly, by explicating the notions of body and autopoiesis, and by reconstructing EAT, not as a conceptual definition of life but as a theoretical identity statement of living beings as a natural kind.